2007
DOI: 10.1080/09603100500428230
|View full text |Cite
|
Sign up to set email alerts
|

How do you straddle hogs and pigs? Ask the Greeks!

Abstract: Evidence of distortions is found in commodity options premiums around informational events. Option Greeks are used to uncover the nature of these distortions in terms of underlying factors. Both changes in underlying futures prices and implied volatility are mispriced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…As proprietary data play an increasingly central role in agricultural decision making, the public sector niche in the market for agricultural information must be reconsidered. (p. 122) In response to this ongoing debate, a number of empirical studies have investigated the economic benefits of public situation and outlook reports using an event study framework (e.g., Colling & Irwin, 1990;Garcia, Irwin, Leuthold, & Yang, 1997;Grunewald, McNulty, & Biere, 1993;McKenzie, Thomsen, & Phelan, 2007;Sumner & Mueller, 1989). Much of this work has focused on USDA crop-production reports and livestock-inventory reports.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As proprietary data play an increasingly central role in agricultural decision making, the public sector niche in the market for agricultural information must be reconsidered. (p. 122) In response to this ongoing debate, a number of empirical studies have investigated the economic benefits of public situation and outlook reports using an event study framework (e.g., Colling & Irwin, 1990;Garcia, Irwin, Leuthold, & Yang, 1997;Grunewald, McNulty, & Biere, 1993;McKenzie, Thomsen, & Phelan, 2007;Sumner & Mueller, 1989). Much of this work has focused on USDA crop-production reports and livestock-inventory reports.…”
Section: Introductionmentioning
confidence: 99%
“…Implied volatility is a forwardlooking measure of volatility that reflects changes in expectations of market participants about future uncertainty. Several studies have shown that the arrival of new information alters the amount of uncertainty that market participants expect to be resolved before option expiration and results in significant changes in optionimplied volatility (e.g., Ederington & Lee, 1996;McKenzie et al, 2007;McNew & Espinosa, 1994;Patell & Wolfson, 1979). Around scheduled news events, resolution of uncertainty is characterized by a rise in implied volatility before the announcement date, a peak on the day before the announcement, and a fall to a new, lower level on the report day (for a hypothetical example, see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant literature has shown that the revelation of information contained in scheduled reports leads to an increase in realized futures price volatility as market expectations are realigned in the immediate aftermath of report release, but that implied volatilities-which are a forward-looking measure of volatility and reflect the expected volatility over the remaining life of an options contract-will fall in the aftermath of a "newsworthy" report. This is because reports contain valuable information and because uncertainty is removed from the market as expectations are realigned (Ederington and Lee 1996;McNew an Espinosa 1994;McKenzie, Thomsen, and Phelan 2007).…”
Section: Applied Economic Perspectives and Policymentioning
confidence: 99%
“…Most of the extant literature investigates what happens to price levels on USDA event days (Adjemian 2012;Ying, Chen and Dorfman 2019) or documents how fast the USDA news is impounded into prices (Adjemian and Irwin 2018;Lehecka, Wang and Garcia 2014). As McNew and Espinosa (1994), A. McKenzie, Thomsen and Phelan (2007), and Isengildina-Massa et al (2008) note, however, one cannot capture the full impact of the USDA reports without also analyzing how they affect market uncertainty and sentiment.…”
Section: Introductionmentioning
confidence: 99%